Latin American growth cycles. Empirical evidence: 1960 - 2000 - Cerro, Ana María; Pineda, José (Estudios de Economía, 2016)
This paper measures and explains to what extent Latin American countries’ growth cycles experienced co-movement in the last forty years, using different methodologies. We find that short lasting cycles showed a great dispersion among cyclical correlation, while long lasting ones displayed considerable co-movement. From the structural VAR approach, the results imply a very low degree of co-movement among the shocks affecting these economies. There exist important differences regarding the speed of adjustment and the excess volatility of demand shocks. Processes of integration among Latin-American countries need more policy coordination prior to any attempt to go further in an economic integration process.